Connected but Fatigued: Virtual Communication, Videoconference Fatigue, and Team Connectedness in Hybrid Work - Nurul Suhesti; Mokhamad Abdul Rozaq; Garry Brumadyadisty; R. Ayu Erni Jusnita; Siska Armawati Sufa (Yayasan Maslahatul Ummah Ilal Jannah, 2026)
Hybrid work has increased employees’ reliance on virtual communication tools for meetings, coordination, task discussion, and team interaction. Although virtual communication can strengthen team connectedness, intensive use may also create videoconference fatigue. This study examines the direct and indirect effects of Virtual Communication Intensity on Perceived Team Connectedness through Videoconference Fatigue among hybrid workers in Surabaya, Indonesia. A quantitative explanatory design was employed using survey data from 200 hybrid workers who used virtual communication tools in formal team settings. The data were analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS. The measurement model demonstrated acceptable reliability, convergent validity, and discriminant validity. The structural model showed that Virtual Communication Intensity had a positive effect on Perceived Team Connectedness and Videoconference Fatigue. Videoconference Fatigue also had a positive effect on Perceived Team Connectedness, contrary to the expected negative direction. The mediation effect was significant but positive, suggesting that fatigue may represent the cost of maintaining connectedness rather than the absence of connectedness. The findings support the idea of a “connected but fatigued” condition in hybrid work, where employees remain socially connected while experiencing fatigue from intensive virtual communication. The study contributes by integrating relational and strain perspectives and provides practical implications for managing virtual communication quality, frequency, and recovery time.